MOVIMIENTOS SOCIALES Y NEOLIBERALISMO EN EL SALVADOR: HUELGA DE MÉDICOS Y TRABAJADORES DEL INSTITUTO SALVADOREÑO DEL SEGURO SOCIAL. - Juárez Ávila, Jorge (2007)
This article analyzes the political and socioeconomic context in which the so-called “strike of physicians and workers of the Instituto Salvadoreño del Seguro Social" developed. The author emphasizes the changes that took place in El Salvador after the Peace Accords, the post-war situation, and the expansion of the neo-liberal policies. Such circumstances set the stage for the development of social conflicts, where new components appeared within the Salvadoran social movement. However, the movement had its moment of reconfiguration where aspects such as innovation and continuity were observed, as shown in this work. In order to understand the importance of these transformations, the author debates with the conceptual and factual components in an attempt to elucidate the impact caused by the neo-liberal policies supported by the right wing governments, represented by the Alianza Republicana Nacionalista (ARENA); the social organization of the strikers; the social motives; the social representations and the liable connection of this movement with the Salvadoran left wing.